Perancangan Ilustrasi Cover Majalah Anak KB Aisyiyah Volume 05 dengan Tema “Liburan Menyenangkan” (International Forum of Researchers and Lecturers, 2024)
This article highlights the crucial role of illustrations as visual elements, especially on the book cover, which serves as the first window for children in their literacy journey. The design aims to produce children's book cover illustrations that are not only visually appealing but also reflective of the themes presented in the book's content. The results of this cover illustration design are expected to contribute positively to creating engaging and relevant learning materials for children participating in the Aisyiyah Playgroup in East Java..